People management: challenges for the voluntary sector - Jiang, Fan (2012)
Have you ever shopped in Oxfam? Have you ever volunteered before? People as the units of the society, have the human nature to help, while voluntary sector is formed to deliver services and help people who need them. We live in it and are also part of it, but do we really know this sector well as the profitable organizations? The voluntary sector has an increasing role in the society, especially the role as an employer. Better performance and services are expected from the public, while in return the need for better and improved human resources management practices is high. In this paper, the difficulties and challenges that are facing by the voluntary organizations nowadays are discussed, and the possible reasons that cause these are presented. Interviews were conducted with 15 participants in total from 5 organizations, and interviews were focus on the skills shortage or gaps, training, motivation and involvement in these organizations. The findings suggest that managers in the voluntary sector are realizing the importance of human resource management within their organizations. But they would have different types of HR practices as they are different from the organizations in the private and public sectors. Limited resources, mixture of workforce and especially the external environment, for example the political and regulation environment, challenge their applying of HR practices in organizations and provide difficulties to organizations. While in the meantime, the labor market slackened a little bit due to the global recession, this provides skilled and knowledgeable people to organizations to remedy their skill shortages or gaps within their organizations.